Islamic Primary Schools in The Netherlands: The Founding, The Debate, and The Outcomes - Geert Driessen (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
At present around 865.000 Muslims live in the Netherlands. In 1988 the first Islamic primary school was founded; now there are 61 with 15,000 students. Islamic education always has been a highly controversial topic in the Netherlands. The debate centers around the question whether the schools contribute to the integration of Muslim youth into Dutch society, or leads to isolation and segregation. This article’s goal is to entangle why and how the schools were established, the obstacles met in this process and the resulting heated societal debate, and the schools’ attainments in terms of cognitive and noncognitive student achievement. To arrive at these insights a review and analysis of the literature was conducted. The results show that Islamic schools academically achieve relatively well, that is, taking into account their largely socioeconomically disadvantaged student population. Also, they perform best on a pen-and-paper integration test. This does not mean, however, that especially populist and right-wing politicians are convinced now that all Muslim youngsters will accept the Dutch norms and values and will integrate into Dutch society.